Feijão-caupi inoculado com diferentes estirpes de rizóbio irrigado com água salina - SOUZA, Luana de Pádua (2018)
Cowpea is a leguminous plant widely cultivated throughout Brazil and each year has gained more visibility. This culture was initially exploited by family farms, however, it has attracted the interest of large producers, who use the technique of irrigation in regions where water scarcity is an obstacle, associated to inoculation with rhizobia strains tolerant to saline and water stress, providing high production under these adverse conditions. The objective of this study was to evaluate the responses of different genotypes of cowpea inoculated with recommended strains, irrigated with saline water, on different blades. The experiment was conducted under field conditions at the Federal Rural University of Pernambuco, Serra Talhada Academic Unit (UFRPE / UAST), Serra Talhada - PE. The experimental design was a randomized block design in a 4 x 2 x 3 factorial scheme, with four replications in sub-divided plots, whose treatments consisted of different irrigation blades – L1, L2, L3 and L4 (28, 36, 44 and 52%), crop evapotranspiration fractions- ETc, associated with genotype (G) of cowpea, as subdivided plot: IPA 206 (G1) and BRS Tumucumaque (G2), two inoculants (I), subdivide plot (BR 3262 (I1) and BR 3267 (I2)) and treatment without inoculant (SI) . The genotype IPA206 showed larger plants, with more leaves, greater fresh and dry mass in flowering and fruiting and high productivity, independent of the irrigation blades used and rhizobia strains. The BRS Tumucumaque genotype presented plants with lower biometric parameters in the shoot compared to the IPA206. The measured parameters related to root and nodules showed that in the greater irrigation blade there was a greater accumulation of root mass. For the nodules, the effect was reversed, at the lowest irrigation blade, there was a greater accumulation. In the largest blade there was the greatest accumulation of nitrogen in the shoot. The PPO and POD activity increased in inoculated plants, mainly in the BRS Tumucumaque, in the highest irrigation blade. In addition, the phenolic compounds in IPA 206 were higher on the lower leaf, and could help to confer tolerance to the studied conditions.